Extraction method of plasma free DNA
By coating modification of Fe3O4 magnetic nanometer microspheres doped with rare earth yttrium and chitosan Schiff base, modified magnetic nanometer microspheres were prepared for efficient extraction of plasma free DNA, solving the problems of cumbersome steps and low efficiency in the prior art, and achieving high purity and high efficiency DNA extraction.
Patent Information
- Application Number
- CN202510141141.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-04-25
AI Technical Summary
The method of extracting free DNA from plasma in the prior art is complicated, has high cost, and the DNA is easily destroyed, resulting in low extraction efficiency and low purity.
Modified magnetic nano-microspheres were prepared by synthesizing Fe3O4 magnetic nano-microspheres doped with rare earth yttrium and coated and modified by the Schiff base reaction of chitosan, and DNA extraction was performed using their responsiveness under a magnetic field.
It improves the extraction efficiency and purity of free DNA in plasma, simplifies the process flow, reduces costs, and the modified magnetic nano microspheres are biodegradable and biocompatible.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
[0001] This application is a divisional application with the application date of June 17, 2024, application number 202410778498.8, and the invention name being a method for extracting free DNA from plasma. Technical Field
[0002] The invention relates to the technical field of biological sample extraction, in particular to a method for extracting plasma free DNA. Background Art
[0003] The DNA of eukaryotic organisms mainly exists in the cell nucleus in the form of chromosomes, but a small part of the DNA is located outside the cell, which is called free DNA. Currently, free DNA is widely used in tumor liquid biopsy. Accurate analysis of free DNA in the blood is of great significance for the early treatment of tumors and screening and monitoring of disease recurrence. However, since free DNA in plasma is a cell-free, fragmented extracellular DNA with a small content and mostly small DNA molecules, its low content makes it difficult to extract, with a large amount of loss and low test sensitivity, which limits its application in clinical diagnosis. Therefore, developing an efficient method for extracting free DNA in plasma is of great significance for clinical medicine and scientific research.
[0004] At present, the improvement measures for the extraction method of free DNA are to remove impurities such as proteins and lipids as much as possible to improve the purity of DNA; on the other hand, it is to enrich free DNA and improve the recovery rate; traditional DNA extraction methods such as phenol-chloroform method and salting-out method are time-consuming and cumbersome due to the presence of liquid-liquid separation, centrifugation and other steps, and DNA may be destroyed under repeated high-speed centrifugation and high shear force, and the use of highly toxic solvents will cause environmental pollution and operator damage, etc., making traditional DNA extraction and separation methods far from suitable for the needs of nucleic acid automation detection. Patent No. CN106011131A discloses a method for separating free nucleic acids from plasma, which uses a silica matrix membrane centrifugal column to separate and purify free nucleic acids, and uses a silica matrix membrane adsorption column to separate free nucleic acids from plasma samples, without the need for organic extraction, completely removing the use of pollutants and inhibitors, and greatly simplifying the process of concentrating and purifying free DNA from plasma. However, the adsorption membrane has a poor enrichment effect on free DNA, resulting in a low concentration of extracted free DNA.
[0005] Magnetic nanoparticles have the advantages of good dispersibility, easy functionalization and easy magnetic separation. Due to the effect of superparamagnetism, magnetic powder can be directed and concentrated under the action of an external magnetic field. After the external magnetic field is removed, it can return to its original structure and form, making the originally complex solid-liquid separation technology faster and simpler. Most of the existing technologies currently use nano Fe3O4 magnetic powder, but nano Fe3O4 particles have high surface energy and are easy to aggregate in tissue fluids. They have problems such as low chemical stability and easy oxidation. There are also technologies that use inorganic nanoparticles to coat the surface of nano Fe3O4, but this will reduce the saturation magnetization intensity of Fe3O4 to a certain extent, affecting the magnetic separation efficiency.
[0006] The invention synthesizes Fe3O4 magnetic nano-microspheres doped with rare earth yttrium to enhance the magnetic separation efficiency, and then prepares quaternized chitosan Schiff base through the Schiff base reaction of chitosan, and coats and modifies the magnetic nano-microspheres. The modified magnetic nano-microspheres are stably dispersed by utilizing the synergistic effect of electrostatic repulsion and steric effect mechanism, thereby enhancing the interaction with DNA and improving the ability of extracting plasma free DNA. The invention also has biodegradability and biocompatibility. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for extracting plasma free DNA, which solves the problems of complicated steps and high cost in the existing methods for extracting plasma free DNA.
[0008] To achieve the above object, the technical solution adopted by the present invention is: A method for extracting free DNA from plasma comprises the following steps: taking 5 centrifuge tubes of 1.5 mL, adding 250 μL of a DNA standard solution and 150 μL of a condensation solution, incubating at room temperature for 5-15 minutes, then adding 50-250 μg of modified magnetic nano-microspheres dispersed in a buffer solution, incubating at room temperature for 10-25 minutes, precipitating the magnetic microspheres using an external magnet, and transferring the supernatant to another 5 centrifuge tubes to prepare a plasma diluent for extracting free DNA.
[0009] The preparation method of the DNA standard solution is as follows: weigh 1.21 g of tris(hydroxymethyl)aminomethane) and 0.37 g of ethylenediaminetetraacetic acid and dissolve them in deionized water; adjust the pH to 4 with 1 M hydrochloric acid solution to obtain a buffer solution; then weigh 10 mg of calf thymus DNA and dissolve it in 10 mL of buffer solution to obtain a 1 mg / mL DNA standard solution.
[0010] Furthermore, the condensation solution was prepared by weighing 1 g of PEG 6000 and 0.78 g of sodium chloride and dissolving them in 5 mL of deionized water to obtain a condensation solution.
[0011] Furthermore, the preparation method of the modified magnetic nanoparticles comprises the following steps: Step S1, dissolving FeCl3·6H2O and YCl3·6H2O in ethylene glycol, stirring for 20-40 min, adding sodium acetate and PEG 6000, and continuing to stir for 30-60 min. After being evenly mixed, transferring the mixed solution to a reactor, stirring for reaction, and after the reaction is completed, naturally cooling to room temperature, magnetic separation, deionized water and ethanol washing, and drying to obtain magnetic nanoparticles.
[0012] Step S2, add chitosan, acetic acid solution and methanol to the reaction flask, stir and swell for 1-3h, add 4-formyl-N,N,N-trimethylaniline, stir and react, filter after the reaction is completed, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base. The preparation process principle is as follows:
[0013] Step S3, adding the freeze-dried magnetic nanoparticles to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 6-7, mechanically stirring at a temperature of 20-35° C. and a rotation speed of 1000-1500 r / min for 8-16 hours, then centrifugally washing in a high-speed centrifuge at 20000-25000 r / min, and freeze-drying to obtain modified magnetic nanoparticles.
[0014] Furthermore, in step S1, the ratio of FeCl3·6H2O, YCl3·6H2O, ethylene glycol, sodium acetate, and PEG 6000 is 1 mol: (0.01-0.05) mol: (8-10) L: (5.4-6.2) mol: (1-2) g.
[0015] Furthermore, in step S1, the reaction temperature is 180-210° C., and the reaction time is 8-16 h.
[0016] Furthermore, in step S2, the ratio of chitosan, acetic acid solution, methanol, and 4-formyl-N,N,N-trimethylaniline is 1 g: (25-35) mL: (30-40) mL: (4.5-6) g.
[0017] Furthermore, the mass fraction of the acetic acid solution in step S2 is 2-5%.
[0018] Furthermore, in step S2, the reaction temperature is 45-60° C., and the reaction time is 3-8 h.
[0019] Furthermore, in step S3, the concentration of the quaternized chitosan Schiff base aqueous solution is 0.05-0.25 g / mL.
[0020] By adopting the above technical solution, the beneficial effects of the present invention are: The invention dopes rare earth yttrium with Fe3O4 to obtain magnetic nano-microspheres, then causes the amino groups on the surface of chitosan to react with the aldehyde groups of 4-formyl-N,N,N-trimethylaniline to produce Schiff base to obtain quaternized chitosan Schiff base, then utilizes electrostatic action to coat the quaternized chitosan Schiff base on the surface of the magnetic nano-microspheres to obtain modified magnetic nano-microspheres, and finally disperses the modified magnetic nano-microspheres in a plasma diluent to be used for extracting free DNA.
[0021] As a new type of solid-phase nucleic acid adsorbent, magnetic nanoparticles have high magnetic field response ability and superparamagnetic properties. Under the action of the magnetic field, they specifically adsorb and desorb DNA through lysis, binding, washing, and elution. This is simple and fast, and the recovered DNA is of high purity. 3+ There are uncoupled electrons in the 4f orbital, which are paramagnetic. After being doped with Fe3O4, the prepared magnetic nanospheres have excellent magnetic properties, which contribute to the efficient magnetic separation of DNA and meet the requirements of DNA extraction from microbial samples.
[0022] Chitosan is a natural polymer material with good biocompatibility and rich in structural active functional groups. By introducing Schiff base and quaternary ammonium salt structures on the surface of chitosan, magnetic nanoparticles can be entangled and connected, and the functional groups can be further modified to provide carriers, reduce nonspecific interactions with biological tissues, and protect the internal magnetic nanoparticles. The modified hydroxyl groups, Schiff bases and other functional groups on the surface of chitosan have the characteristics of reversible adsorption of DNA. Schiff base compounds bind to DNA molecules through π-π stacking, thereby achieving the purpose of controlling DNA adsorption and dissociation and reducing nonspecific adsorption with other impurities. In the process of DNA extraction, magnetic nanoparticles with cationic quaternary chitosan on the surface can effectively bind to DNA with anions, and DNA can be fixed on the surface of magnetic microspheres through different binding methods such as electrostatic effects, thereby achieving the purpose of separation and purification.
[0023] The method for extracting free DNA from plasma provided by the present invention can prevent free radicals from damaging the free DNA structure during the process of extracting free DNA, thereby ensuring the integrity of the extracted free DNA, facilitating subsequent prenatal diagnosis and early tumor screening, and the extraction process is simple, suitable for large-scale promotion and application. DETAILED DESCRIPTION
[0024] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] Preparation of 4-formyl-N,N,N-trimethylaniline: Add 1.49mmol of p-diaminobenzaldehyde and 5mL of acetone to a reaction flask, stir evenly, add 30mmol of iodomethane, react at 70°C for 10h, filter, wash the filter cake with ether, and dry to obtain 4-formyl-N,N,N-trimethylaniline. The preparation process is as follows:
[0026] Preparation of buffer solution: 1.21 g of tris(hydroxymethyl)aminomethane and 0.37 g of ethylenediaminetetraacetic acid were weighed and dissolved in deionized water, and the pH was adjusted to 4 with 1 M hydrochloric acid solution to obtain a buffer solution.
[0027] Preparation of DNA standard solution: Weigh 10 mg of calf thymus DNA and dissolve it in 10 mL of buffer to obtain a 1 mg / mL DNA standard solution.
[0028] Preparation of condensation solution: Weigh 1 g of PEG 6000 and 0.78 g of sodium chloride and dissolve them in 5 mL of deionized water to obtain a condensation solution.
[0029] Example 1 10 mmol of FeCl3·6H2O and 0.1 mmol of YCl3·6H2O were dissolved in 90 mL of ethylene glycol and stirred for 30 min. 60 mmol of sodium acetate and 150 g of PEG 6000 were added and stirred for 50 min. After being mixed evenly, the mixture was transferred to a reactor and reacted at 200°C for 15 h. The mixture was naturally cooled to room temperature, and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing, and drying.
[0030] Example 2 10 mmol of FeCl3·6H2O and 0.2 mmol of YCl3·6H2O were dissolved in 80 mL of ethylene glycol and stirred for 20 min. 54 mmol of sodium acetate and 10 g of PEG 6000 were added and stirred for 30 min. After being mixed evenly, the mixture was transferred to a reactor and reacted at 210°C for 8 h. The mixture was naturally cooled to room temperature and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing, and drying.
[0031] Example 3 10 mmol of FeCl3·6H2O and 0.3 mmol of YCl3·6H2O were dissolved in 100 mL of ethylene glycol and stirred for 40 min. 62 mmol of sodium acetate and 20 g of PEG 6000 were added and stirred for 60 min. After being mixed evenly, the mixture was transferred to a reactor and reacted at 180°C for 16 h. The mixture was naturally cooled to room temperature and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing and drying.
[0032] Example 4 10 mmol of FeCl3·6H2O and 0.4 mmol of YCl3·6H2O were dissolved in 95 mL of ethylene glycol and stirred for 35 min. 55 mmol of sodium acetate and 16 g of PEG 6000 were added and stirred for 40 min. After being mixed evenly, the mixture was transferred to a reactor and reacted at 200°C for 10 h. The mixture was naturally cooled to room temperature, and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing, and drying.
[0033] Example 5 10 mmol of FeCl3·6H2O and 0.5 mmol of YCl3·6H2O were dissolved in 95 mL of ethylene glycol, stirred for 25 min, 56 mmol of sodium acetate and 18 g of PEG 6000 were added, and stirring was continued for 50 min. After being mixed evenly, the mixture was transferred to a reactor, reacted at 190°C for 12 h, naturally cooled to room temperature, and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing, and drying.
[0034] Comparative Example 1 10 mmol of FeCl3·6H2O was dissolved in 90 mL of ethylene glycol and stirred for 30 min. 60 mmol of sodium acetate and 150 g of PEG 6000 were added and stirred for 50 min. After being mixed evenly, the mixture was transferred to a reactor and reacted at 200°C for 15 h. The mixture was naturally cooled to room temperature, and magnetic nanospheres were obtained after magnetic separation, deionized water and ethanol washing, and drying.
[0035] Magnetic property test: Weigh 100 mg of magnetic nanospheres, wrap them with sulfuric acid paper into the size of rice grains, and measure the saturation magnetization intensity of the sample by a vibrating magnetometer.
[0036] Saturation magnetization (emu / g) Example 1 70.13 Example 2 75.42 Example 3 84.38 Example 4 88.26 Example 5 87.69 Comparative Example 1 66.81 Generally speaking, the higher the saturation magnetization of a material, the better its magnetic properties. As can be seen from the test results in the table above, with the increase of the rare earth yttrium doping amount, the saturation magnetization of the magnetic nano-microspheres is enhanced, and Example 4 reaches 88.26emu / g. This is because the rare earth Y 3+ There are uncoupled electrons in the 4f orbital, which exhibit paramagnetism. After being composite-doped with Fe3O4, the prepared magnetic nanospheres have excellent magnetic properties, which are conducive to the efficient magnetic separation of DNA. In Comparative Example 1, no rare earth yttrium element was added, and its saturation magnetization intensity was only 66.81emu / g, and the magnetic properties were inferior to those of the embodiment.
[0037] Example 6 (1) Add 2 g of chitosan, 60 mL of 3% acetic acid solution and 70 mL of methanol into a reaction flask, stir and swell for 2 h, add 10 g of 4-formyl-N,N,N-trimethylaniline, react at 55 °C for 6 h, filter, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base.
[0038] (2) The freeze-dried magnetic nanoparticles (prepared in Example 4) were added to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 7 and a concentration of 0.05 g / mL, and mechanically stirred at a temperature of 25°C and a rotation speed of 1200 r / min for 10 h. The mixture was then centrifuged and washed in a high-speed centrifuge at 22000 r / min, and freeze-dried to obtain modified magnetic nanoparticles.
[0039] (3) Take 5 1.5 mL centrifuge tubes, add 250 μL of DNA standard solution and 150 μL of condensation solution, and incubate at room temperature for 10 min. Then add 50 μg of modified magnetic nanoparticles dispersed in buffer solution and incubate at room temperature for 15 min. Use an external magnet to precipitate the magnetic nanoparticles and transfer the supernatant to another 5 centrifuge tubes to prepare plasma diluent for the extraction of free DNA.
[0040] Example 7 (1) Add 5 g of chitosan, 125 mL of 2% acetic acid solution and 150 mL of methanol into a reaction flask, stir and swell for 3 h, add 22.5 g of 4-formyl-N,N,N-trimethylaniline, react at 60 °C for 3 h, filter, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base.
[0041] (2) The freeze-dried magnetic nanoparticles (prepared in Example 4) were added to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 7 and a concentration of 0.1 g / mL, and mechanically stirred at a temperature of 35°C and a rotation speed of 1500 r / min for 8 h. The magnetic nanoparticles were then centrifuged and washed in a high-speed centrifuge at 25000 r / min, and freeze-dried to obtain modified magnetic nanoparticles.
[0042] (3) Take 5 1.5 mL centrifuge tubes, add 250 μL of DNA standard solution and 150 μL of condensation solution, and incubate at room temperature for 15 min. Then, add 100 μg of modified magnetic nanoparticles dispersed in buffer solution and incubate at room temperature for 25 min. Use an external magnet to precipitate the magnetic nanoparticles and transfer the supernatant to another 5 centrifuge tubes to prepare plasma diluent for the extraction of free DNA.
[0043] Example 8 (1) Add 1 g of chitosan, 35 mL of 5% acetic acid solution and 40 mL of methanol into a reaction flask, stir and swell for 1 h, add 6 g of 4-formyl-N,N,N-trimethylaniline, react at 45 °C for 8 h, filter, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base.
[0044] (2) The freeze-dried magnetic nanoparticles (prepared in Example 4) were added to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 6 and a concentration of 0.15 g / mL, and mechanically stirred at a temperature of 20°C and a rotation speed of 1000 r / min for 16 h. The mixture was then centrifuged and washed in a high-speed centrifuge at 20000 r / min, and freeze-dried to obtain modified magnetic nanoparticles.
[0045] (3) Take 5 1.5 mL centrifuge tubes, add 250 μL of DNA standard solution and 150 μL of condensation solution, and incubate at room temperature for 15 min. Then add 150 μg of modified magnetic nanoparticles dispersed in buffer and incubate at room temperature for 10 min. Use an external magnet to precipitate the magnetic nanoparticles and transfer the supernatant to another 5 centrifuge tubes to prepare plasma diluent for the extraction of free DNA.
[0046] Example 9 (1) Add 10 g of chitosan, 300 mL of 3% acetic acid solution and 360 mL of methanol into a reaction flask, stir and swell for 2 h, add 50 g of 4-formyl-N,N,N-trimethylaniline, react at 55 °C for 7 h, filter, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base.
[0047] (2) The freeze-dried magnetic nanoparticles (prepared in Example 4) were added to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 7 and a concentration of 0.2 g / mL, and mechanically stirred at a temperature of 30°C and a rotation speed of 1300 r / min for 12 h. The mixture was then centrifuged and washed in a high-speed centrifuge at 24000 r / min, and freeze-dried to obtain modified magnetic nanoparticles.
[0048] (3) Take five 1.5 mL centrifuge tubes, add 250 μL of DNA standard solution and 150 μL of condensation solution, and incubate at room temperature for 15 min. Then, add 200 μg of modified magnetic nanoparticles dispersed in buffer and incubate at room temperature for 20 min. Use an external magnet to precipitate the magnetic nanoparticles, and transfer the supernatant to another five centrifuge tubes to prepare plasma diluent for the extraction of free DNA.
[0049] Example 10 (1) Add 3 g of chitosan, 96 mL of 5% acetic acid solution and 105 mL of methanol into a reaction flask, stir and swell for 3 h, add 16.5 g of 4-formyl-N,N,N-trimethylaniline, react at 60 °C for 5 h, filter, wash the filter cake with saturated sodium bicarbonate and deionized water, and dry to obtain quaternized chitosan Schiff base.
[0050] (2) The freeze-dried magnetic nanoparticles (prepared in Example 4) were added to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 7 and a concentration of 0.25 g / mL, and mechanically stirred at a temperature of 25°C and a rotation speed of 1500 r / min for 15 h. The mixture was then centrifuged and washed in a high-speed centrifuge at 25000 r / min, and freeze-dried to obtain modified magnetic nanoparticles.
[0051] (3) Take five 1.5 mL centrifuge tubes, add 250 μL of DNA standard solution and 150 μL of condensation solution, and incubate at room temperature for 15 min. Then, add 250 μg of modified magnetic nanoparticles dispersed in buffer and incubate at room temperature for 25 min. Use an external magnet to precipitate the magnetic nanoparticles, and transfer the supernatant to another five centrifuge tubes to prepare plasma diluent for the extraction of free DNA.
[0052] Comparative Example 2 DNA was extracted from plasma dilutions using the conventional phenol-chloroform method.
[0053] Magnetic property test: Weigh 100 mg of modified magnetic nanospheres, wrap them with sulfuric acid paper into the size of rice grains, and measure the saturation magnetization intensity of the sample by a vibrating magnetometer.
[0054] Saturation magnetization (emu / g) Example 4 88.26 Example 6 86.13 Example 7 85.42 Example 8 82.38 Example 9 80.26 Example 10 79.69 From the test results in the above table, it can be seen that with the increase of the concentration of the quaternized chitosan Schiff base aqueous solution, the saturation magnetization intensity of the modified magnetic nanoparticles decreases, but the decrease is not large and is still higher than the saturation magnetization intensity of pure Fe3O4. This is because the polymer surface is magnetically inert, which reduces the magnetic properties after coating Fe3O4. However, the modified magnetic nanoparticles still have strong enough superparamagnetism to meet the magnetic separation requirements of DNA.
[0055] The adsorption efficiency and maximum adsorption capacity of modified magnetic microspheres for DNA at a wavelength of 260 nm were tested by ultraviolet spectrophotometer. The adsorption efficiency = (C0-C1) / C0×100%; the maximum adsorption capacity Q = V×(C0-C1) / m; where C0 is the initial concentration of DNA (mg / mL); C1 is the residual concentration of DNA (mg / mL); V represents the volume of the reaction system; and m represents the mass of the magnetic microspheres used (mg).
[0056] Maximum adsorption capacity (μg / 250μg) Adsorption efficiency (%) Example 6 210.15 84.06 Example 7 223.70 89.48 Example 8 236.31 94.52 Example 9 245.24 98.09 Example 10 245.69 98.27 Comparative Example 2 143.57 57.43 It can be seen from the test results in the above table that with the increase of the content of modified magnetic microspheres, the maximum adsorption capacity of DNA gradually increases, indicating that DNA is successfully adsorbed on the surface of the modified magnetic microspheres, the maximum adsorption capacity reaches 245.69μg / 250μg, and the adsorption efficiency reaches up to 98.27%, which is a high adsorption efficiency; this is because the prepared modified magnetic nanospheres use polysaccharide molecules to entangle and connect the magnetic nanoparticles, which protect the internal magnetic nanoparticles, and the modified hydroxyl groups and Schiff bases on the surface of chitosan fix DNA on the surface of the magnetic microspheres through electrostatic action to achieve the purpose of separation and purification; at the same time, the magnetic nanoparticles with cationic quaternized chitosan on the surface can effectively combine with DNA with anions, thereby achieving the purpose of controlling DNA adsorption, dissociation and reducing nonspecific adsorption with other impurities, so it has greater adsorption efficiency and adsorption capacity, simple process and strong feasibility.
[0057] Comparative Example 2 is a traditional phenol-chloroform method for extracting DNA, which has a small amount of DNA adsorption, low adsorption efficiency and high reagent toxicity, making the DNA purification preparation process complicated.
[0058] Magnetic response time test: Take 2 mL of the supernatant in the example and ultrasonically disperse it for 10 minutes, then put it into the magnetic sample holder and start timing. The timing ends when the supernatant is completely clear. The required time is the magnetic response time of the sample. The average value is taken after 3 measurements.
[0059] Magnetic response time (s) DNA recovery rate (%) Example 6 31 75.3 Example 7 25 80.5 Example 8 20 87.2 Example 9 13 92.7 Example 10 10 95.6 Magnetic response time refers to the time it takes for DNA extraction magnetic beads to be completely magnetically separated after being placed on the magnetic rack. The magnetic response time should not be too long. Too long a magnetic response time will prolong the waiting time and reduce the operating experience. From the test results in the above table, it can be seen that the more modified magnetic microspheres are added, the shorter the magnetic response time and the higher the DNA recovery rate. This is because a longer magnetic response time will cause some adsorbed DNA to be unable to be completely recovered, affecting the recovery rate. Therefore, magnetic nano-microspheres can achieve instantaneous separation of trace amounts of DNA under a magnetic field, are easy to automate, have a high recovery rate, and can be widely promoted and used.
[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A modified magnetic nanoparticle, characterized in that: The preparation method of the modified magnetic nanoparticles comprises the following steps: Step S1, dissolving FeCl3·6H2O and YCl3·6H2O in ethylene glycol, stirring for 20-40 min, adding sodium acetate and PEG6000, and continuing to stir for 30-60 min. After being evenly mixed, transferring the mixed solution to a reactor, stirring for reaction, and cooling naturally to room temperature after the reaction is completed, performing magnetic separation, washing with deionized water and ethanol, and drying to obtain magnetic nanoparticles; Step S2, adding chitosan, acetic acid solution and methanol into a reaction flask, stirring and swelling for 1-3 hours, adding 4-formyl-N,N,N-trimethylaniline, stirring and reacting, filtering after the reaction is completed, washing the filter cake with saturated sodium bicarbonate and deionized water, and drying to obtain quaternized chitosan Schiff base; Step S3, adding the freeze-dried magnetic nanoparticles to a quaternary ammonium chitosan Schiff base aqueous solution with a pH of 6-7, mechanically stirring at a temperature of 20-35° C. and a rotation speed of 1000-1500 r / min for 8-16 hours, then centrifugally washing in a high-speed centrifuge at 20000-25000 r / min, and freeze-drying to obtain modified magnetic nanoparticles; In the step S1, the ratio of FeCl3·6H2O, YCl3·6H2O, ethylene glycol, sodium acetate, and PEG 6000 is 1 mol: (0.01-0.05) mol: (8-10) L: (5.4-6.2) mol: (1-2) g; In step S2, the ratio of chitosan, acetic acid solution, methanol, and 4-formyl-N,N,N-trimethylaniline is 1 g: (25-35) mL: (30-40) mL: (4.5-6) g; The mass fraction of the acetic acid solution in step S2 is 2-5%; The concentration of the quaternized chitosan Schiff base aqueous solution in step S3 is 0.05-0.25 g / mL.
2. The modified magnetic nanoparticles according to claim 1, characterized in that: In step S1, the reaction temperature is 180-210° C. and the reaction time is 8-16 hours.
3. The modified magnetic nanoparticles according to claim 1, characterized in that: In step S2, the reaction temperature is 45-60° C. and the reaction time is 3-8 h.
4. Use of the modified magnetic nanoparticles as claimed in claim 1 in a method for extracting free DNA from plasma.
Citation Information
Patent Citations
Method for separating free nuclei free nucleic acids from plasma
CN106011131A